The Times Atlas of the 20th Century - Edited by Overy, Richard (London Times Books, 1996)
This work covers every major event of the 20th century from the pomp of the imperial world of 1900 to the uncertain stumblings of today's New World
Include Color Illustration and Index
Keywords: Chronology, Historical -- Civilization